The Effects of Teaching Strategic and Self-Confidence on Students’ Speaking Competency (An Experimental in the 8th Grade Students of SMP Muslimin Panyawungan) - Dini Rizki Rahayu (Publikasi Indonesia, 2025)
The aim of this study was to investigate the effect of the Think-Pair-Share teaching strategy and self-confidence on students’ speaking competency. This study was conducted with 8th-grade students of SMP Muslimin Panyawungan in the academic year 2023/2024. There were 99 students selected as the sample and divided into experimental and control groups. The study used a post-test-only control group design. The analysis was conducted using MANOVA facilitated by SPSS version 21.0 for Windows. The results indicated that (1) there was a significant effect of Think-Pair-Share on students’ speaking competency ( , ); (2) there was a significant effect of self-confidence on students’ speaking competency ( , ); and (3) simultaneously, there was a significant effect of Think-Pair-Share and students’ self-confidence on students’ speaking competency ( ).